THE EFFECT OF WORKING CAPITAL, PRODUCTION COSTS, DISTRIBUTION COSTS, MARKETING COSTS AND SALES ON NET PROFIT AT YUN'S COLLECTION HOUSEHOLD INDUSTRY - Nanda Fitrias Siti Rohana (State Islamic Institute (IAIN) Tulungagung, 2022)
This study hopes to conclude the impact of working capital, creation costs, conveyance costs, promoting expenses, and deals volume on the benefits of the Yun's Collection home industry organization in 2016-2020 either to some degree or at the same time. The methodology utilized in this exploration is quantitative. The populace utilized is the Yun's Collection home industry, while the examination test is the proprietor of the Yun's Collection home industry. The information utilized is essential information with interview information assortment strategies and documentation.The information examination procedure utilized different direct relapse investigation helped by SPSS 16.0 programming. The consequences of the investigation show that to some degree working capital, creation costs, showcasing expenses and deals volume altogether affect total compensation, while appropriation costs meaningfully affect overall gain. All the while, working capital, creation costs, conveyance costs, promoting expenses, and deals volumes essentially affect the benefits of Yun's Collection home industry organizations in 2016-2020.